The Determination of Phosphor Status in Leaf Tissues to Make a Fertilizer Recommendation and Predict Mangosteen Yield - Kurniadinata, Odit F.; Poerwanto, Roedhy; Susila, Anas D. (Journal of Tropical Horticulture, 2018)
Mangosteen (GarciniamangostanaL.) knows as one of the most delicious fruit in the word, itâ€™s call as â€œQueen of fruitsâ€. The problems in mangosteen culture are low productivity and low fruit quality due to less developed technical culture, especially on fertilizer. There is a little information available on mangosteen fertilizer recommendation standards based on scientific experiment.Phosphor fertilizer increased growth especially in the generative stage of mangosteen. Phosphor increases the number of flowers and fruits set. It also decreases the number of flowers and fruits drop, with a linear response. It indicates mangosteen trees absorb phosphor to increase the vegetative growth and support production. Fertilizers increase phosphor concentrations in leaf tissues. Leaf tissues analyses showed the status of phosphor status, This status has a correlation to the yield. The higher the nutrients concentration in the leaf tissues, the higher the mangosteens yield in the next harvest